Reversible Testicular Toxicity of Piperine on Male Albino Rats - Chinta, Gopichand (Pharmacogn Mag, 2017)
BACKGROUND: Piperine was widely used in traditional medicine for inducing sterility and abortion. OBJECTIVE: To evaluate the effect of the piperine on testis of male albino rats MATERIALS AND METHODS: Adult male rats were divided into four groups (n = 12). Group I (control): Rats were given vehicle p.o. i.e. 0.5% carboxymethyl cellulose in normal saline daily for 60 days, Group II (ED): Rats received piperine at a dose of 10 mg/kg body weight (b.w.) daily, Group III (E4D): Rats received piperine at a dose of 10 mg/kg b.w. on every 4(th) day, Group IV (E7D): Rats received piperine at a dose of 10 mg/kg b.w. on every 7(th) day. Half of the animals from each group were sacrificed after the treatment period (60 days), and the remaining were kept for drug-free withdrawal period (60 days) and then sacrificed. RESULTS: Piperine significantly decreased the reproductive organ weights in groups ED and E4D. Piperine induced hormonal imbalance by altering the serum levels of follicle-stimulating hormone, luteinizing hormone, sex hormone binding globulin, serum, and testicular testosterone in groups ED and E4D. Furthermore, piperine decreased the activity of germ cell markers and Leydig cellular steroidogenic enzymes in the groups ED and E4D after 60 days. All the above-altered values returned to normal levels after withdrawal period. Histopathological findings also supported the above findings. CONCLUSION: From the above data, it can be concluded that piperine could be a good lead molecule for the development of reversible oral male contraceptive. SUMMARY: Piperine was employed for the contraceptive purposes in traditional medicine. Piperine significantly impaired the spermatogenesis by decreasing the testicular hormone synthesis in groups ED and E4D. Piperine disrupted the testicular antioxidant system by promoting the ROS production and hydroxyl radical generation in rat testis in groups ED and E4D. Histopathological evidence supported the disruption of spermatogenesis by piperine. All the effects of piperine after the treatment period (i.e. 60 days) were back to normal after the withdrawal period (i.e., after 120 days). [Image: see text]